2019
DOI: 10.3390/metabo9070137
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Interval Training Decreases Resting Urinary Hypoxanthine Concentration in Young Active Men—A Metabolomic Approach

Abstract: High-intensity interval training (HIIT) is known to improve performance and skeletal muscle energy metabolism. However, whether the body’s adaptation to an exhausting short-term HIIT is reflected in the resting human metabolome has not been examined so far. Therefore, a randomized controlled intervention study was performed to investigate the effect of a ten-day HIIT on the resting urinary metabolome of young active men. Fasting spot urine was collected before (−1 day) and after (+1 day; +4 days) the training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 74 publications
2
19
0
Order By: Relevance
“…In highly-trained athletes, but not in the control group, the increased amount of intense training loads in the subsequent phases of the annual training cycle resulted in adaptive changes in plasma purine derivatives concentration. The significantly lowest levels of plasma Ino and Hx in the competition phase indicate either their reduced release from the skeletal muscle [20,21] or their more effective reutilization to IMP and further incorporation to the adenylate pool through a purine nucleotide cycle (not present in RBC) [22]. Our observation that high-intensity training brings about reduced purine loss is consistent with earlier findings.…”
Section: Plasma Purine Derivativessupporting
confidence: 91%
See 2 more Smart Citations
“…In highly-trained athletes, but not in the control group, the increased amount of intense training loads in the subsequent phases of the annual training cycle resulted in adaptive changes in plasma purine derivatives concentration. The significantly lowest levels of plasma Ino and Hx in the competition phase indicate either their reduced release from the skeletal muscle [20,21] or their more effective reutilization to IMP and further incorporation to the adenylate pool through a purine nucleotide cycle (not present in RBC) [22]. Our observation that high-intensity training brings about reduced purine loss is consistent with earlier findings.…”
Section: Plasma Purine Derivativessupporting
confidence: 91%
“…Our observation that high-intensity training brings about reduced purine loss is consistent with earlier findings. Following a 1-and 4-day high-intensity interval training (HIIT), a decreased urinary Hx concentration was shown in young active men, signifying a training-induced adaptation in purine nucleotide metabolic pathways [21]. Stathis, et al [20] observed that in recreationally active individuals the skeletal muscle concentration of Ino was reduced after a 30-second sprint performance test after a seven-week sprint training, which indicated a reduction of exercise purine loss.…”
Section: Plasma Purine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed deviations may be in part artificial and are probably related to the applied background subtraction procedure, since no bias >10% was observed for isotope‐labelled compounds, for which no background subtraction was necessary. Moreover, a recent method comparison with 1 H‐NMR demonstrated excellent correlation in urine, with R 2 >0.87 for those compounds which were accessible with both methods . For plasma, the estimated accuracy was as good as for urine, at least for the majority of compounds.…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, a recent method comparison with 1 H-NMR demonstrated excellent correlation in urine, with R 2 >0.87 for those compounds which were accessible with both methods. 48 For plasma, the estimated accuracy was as good as for urine, at least for the majority of compounds. However, some compounds showed a somewhat lower accuracy, especially those with histidine or arginine moieties.…”
Section: Methods Validationmentioning
confidence: 85%